STRENGTHENING YOUNG GENERATION CHARACTERS IN THE DISRUPTION ERA THROUGH THE INTERNALIZATION OF WAYANG GOLEK VALUES - Abdul Azis; Kokom Komalasari; Iim Siti Masyitoh (Sosiohumaniora, 2020)
As a adiluhung (valuable art), Wayang Golek performances can contribute to the strengthening of the character of the young generation in facing various challenges in the era of disruption. This is very important, considering that in the era of disruption such as the current challenge for the younger generation in facing the industrial era 4.0 is the loss of character as an Indonesian nation. This study aims to reveal the contribution of Wayang Golek performances values to the strengthening of the character of the younger generation in the era of disruption. The research approach used is qualitative with ethnographic methods, so that it can describe the character values contained in the Wayang Golek performances that are relevant to the character of the Indonesian nation. The results showed that the values of the Wayang Golek performances could contribute to the strengthening of the character of the younger generation. This is because the puppet show is aesthetically designed as an art performance that contains elements of the spectacle as well as guidance. This means, in addition to entertaining through humorous jokes, the Wayang Golek performance is able to give a moral message to the audience about the importance of religious values and nationalism in the face of changing times.